2003
DOI: 10.1021/ja029528p
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Dependent Photochemistry of Diazo Meldrum's Acid and Its Spirocyclic Isomer, Diazirino Meldrum's Acid:  Wolff Rearrangement versus Isomerization

Abstract: Photoreaction of diazo Meldrum's acid (1) shows a unique wavelength selectivity. At 254 nm it results in efficient (phi(254) = 0.34) Wolff rearrangement, while irradiation with 355 nm light leads to a completely different process, isomerization into corresponding cyclic alpha,alpha"-dicarbonyl diazirine 2 (phi(350) = 0.024). UV photolysis of diazirine 2 is accompanied by two competing processes: loss of nitrogen followed by the Wolff rearrangement and isomerization into diazo compound 1. Thermal decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 13 publications
0
27
1
1
Order By: Relevance
“…It is interesting that thermolysis carried out in more polar reaction media (MeOH, 40°C) in practice gave the diazo compound 140a quantitatively. [101] Moreover, the diazirine 139a rapidly turns into the diazo isomer 140a in thermal fashion only in solution, remaining unchanged over several months in crystalline form. [102] The results obtained were confirmed by calculations relating to the potential energy barrier to the thermal isomerization of the diazirine to the diazo compound in the gas phase (about 30-37 kcal mol -1 ).…”
Section: Spirocyclic Dialkyl Diazirine-33-dicarboxylatesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting that thermolysis carried out in more polar reaction media (MeOH, 40°C) in practice gave the diazo compound 140a quantitatively. [101] Moreover, the diazirine 139a rapidly turns into the diazo isomer 140a in thermal fashion only in solution, remaining unchanged over several months in crystalline form. [102] The results obtained were confirmed by calculations relating to the potential energy barrier to the thermal isomerization of the diazirine to the diazo compound in the gas phase (about 30-37 kcal mol -1 ).…”
Section: Spirocyclic Dialkyl Diazirine-33-dicarboxylatesmentioning
confidence: 99%
“…[116] Numerous data on the behavior of cyclic diazodicarbonyl compounds have given new impetus to a revision of the properties of their linear analogues (Scheme 56). [80,101] It has been reported that irradiation of the diazomalonic ester 136 (UV: 251, 344 nm) at room temperature leads to the formation of two main products: the methoxymalonate 137 (elimination of nitrogen) and the diazirine 135 (isomerization, UV: 244, 291 nm).…”
Section: Diazodiestersmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct irradiation (λ > 210 nm) of diazodiketones 1 gives rise to accumulation of one of their upper singlet excited states 1 ( 1 )* [13,15,18,20,4951] which turn into usual Wolff rearrangement products, i.e., highly reactive oxoketenes 6 (Scheme 2, reaction I). The intermediate ketenes 6 react with H 2 O or MeOH present in the reaction mixture to give 2-oxocarboxylic acid 4a or esters 5a–c .…”
Section: Resultsmentioning
confidence: 99%
“…The position of these absorbance bands is virtually independent from the polarity of the solvents used, and thus does not allow a confident Scheme 1 assignment to the relevant transitions. However, by analogy with other diazocarbonyl compounds [13 -16], these absorptions can be evidently attributed to p -p* and n -p* electronic transitions, respectively (see also [17] (Schemes 2 and 3). Irradiation was carried out in a quartz vessel with UV light of a medium-pressure Hg lamp (l > 210 nm) under an O 2 -free atmosphere until complete disappearance of 1a or 1b in the reaction mixture (by TLC; normally 1.5 -2 h).…”
mentioning
confidence: 86%